Data "OFS 2025 Manuscript Data - FSI Humidity Sensors" - Wiseman, Kieran B.; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2024)
This research demonstrates a novel approach to distributed humidity sensing using polyimide-coated optical fibres and fibre segment interferometry (FSI). FSI interrogates the cumulative strain along fibre segments formed between pairs of FBG reflectors, significantly enhancing sensitivity by scaling with segment length. Polyimide, a hygroscopic coating material, induces strain on the optical fibre in response to humidity changes, creating measurable phase shifts. Experiments were conducted using an FSI array comprising three 10 mm fibre segments, with polyimide coatings on two segments and the third uncoated for control. This work highlights the advantages of FSI over direct FBG interrogation, including increased sensitivity, scalability, and reduced complexity of interrogation hardware.
Two .csv files comprising the total data set. One contains two columns of data for an independent RH sensor, with headers of "Time_Sensor (s)" and "RH(%)". The second .csv file contains five columns of data for the multiplexed interferometers, with headers of "Time (s)", "Int1 (rad)", "Int2 (rad)", "Int3(rad)", "Int4 (rad)".
Keywords: fibre; humidity; sensor; distributed; polyimide; coated; optical